2015
DOI: 10.3389/fncel.2015.00392
|View full text |Cite
|
Sign up to set email alerts
|

Breaking down the barriers: the gut microbiome, intestinal permeability and stress-related psychiatric disorders

Abstract: The emerging links between our gut microbiome and the central nervous system (CNS) are regarded as a paradigm shift in neuroscience with possible implications for not only understanding the pathophysiology of stress-related psychiatric disorders, but also their treatment. Thus the gut microbiome and its influence on host barrier function is positioned to be a critical node within the brain-gut axis. Mounting preclinical evidence broadly suggests that the gut microbiota can modulate brain development, function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
659
1
25

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 834 publications
(698 citation statements)
references
References 313 publications
(268 reference statements)
13
659
1
25
Order By: Relevance
“…These transmembrane proteins connect with the opposing plasma membrane, thereby forming a mechanical link between epithelial cells and establishing a barrier to paracellular. It has been shown that the structure of the intestinal barrier is formed by the end of the first trimester of pregnancy (Kelly et al, 2015). Epithelial cells with microvilli, goblet, and enteroendocrine cells appear by week 8 of gestation and tight junctions are detected from week 10.…”
Section: Microbes Gut Barrier and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…These transmembrane proteins connect with the opposing plasma membrane, thereby forming a mechanical link between epithelial cells and establishing a barrier to paracellular. It has been shown that the structure of the intestinal barrier is formed by the end of the first trimester of pregnancy (Kelly et al, 2015). Epithelial cells with microvilli, goblet, and enteroendocrine cells appear by week 8 of gestation and tight junctions are detected from week 10.…”
Section: Microbes Gut Barrier and Inflammationmentioning
confidence: 99%
“…The main function of the intestinal barrier is to regulate the absorption of nutrients, electrolytes, and water from the lumen into the circulation and to prevent the entry of pathogens and toxins (Kelly et al, 2015). Furthermore, regulation of the exchange of molecules between the environment and the host through the intestinal barrier influences the equilibrium between tolerance and immunity to self and non-self-antigens (Fasano, 2011).…”
Section: Microbes Gut Barrier and Inflammationmentioning
confidence: 99%
“…34 There is also evidence for alterations in microbiota balance in IBS and alterations in the bidirectional communication between the gut microbiota, the CNS, and the enteric nervous system. 35,36 …”
Section: Pathophysiology Of Irritable Bowel Syndrome: Activation Of Tmentioning
confidence: 99%
“…In the context of diseases of unknown etiology and with no available prevention or cure, man-microbe symbiosis was shown to be durably altered in conjunction with reciprocal aggravating signals. For instance, altered microbiota could promote intestinal hyperpermeability and inflammation, the latter promoting oxidative stress aggravating microbiota alteration [15][16][17]). …”
Section: What Are the Tools For Studying Microbiota?mentioning
confidence: 99%